PENGEMASAN MATERI PEMBELAJARAN AUDIO VISUAL TARI TERANG BULAN BERBASIS WEBSITE UNTUK KELAS X SEKOLAH MENEGAH ATAS - Sapitri Sirait; Tuti Rahayu (Universitas Negeri Medan, 2020)
ABSTRACTThis study aims to describe the packaging stages and produce Terang Bulan dance learning products in the form of Website-based audio visual media for Class X High School. Theories used in the research topic are packaging theory, learning materials, audio visual media and Website Based Learning The theory used in this research is the Theory of Steps for Packaging Material Based Learning Websites according to Lu'mu Tasri (2011: 17). The population in this study were students of the 2015 Bandung Dance Education Study Program and the sample in this study were 2 students of the 2015 Dance Education Education Study Program and Aunt Petti Manik as the resource persons in this study. Data collection techniques include field observations, interviews, documentation and literature studies. This research uses descriptive qualitative method. Analysis of media expert validation and material expert validation use a Likert scale to calculate the overall average. This research was conducted at the Dance Studio of Dance Education Study Program at the Faculty of Language and Arts Department of Dance for the packaging process carried out at the Laboratory of Dance Education Study Program at the Faculty of Dance. The results of the study note that there are 10 stages in packaging learning products for Terang Bulan Dance Material in the form of Website-based audio visual media for Class X Senior High School consisting of (1) determining the target of learning material (2) choosing a topic that suits the needs of the target (3) making material map (4) formulation of learning objectives (5) preparation of evaluation tools (6) collection of references (7) preparation of materials (8) editing (9) upload (10) testing. In the Validation stage, product validation involves 2 material expert validators and 1 media expert validator. This product gets a very good category with a detailed score of 4.6 from the material expert validation test, a score of 4.8 from the media expert validation test. The score proves that this learning video product is very good to be applied in the learning process of Culture and Art especially the Dance Class X High School. Students can learn this dance not only in the KBM process takes place or while in the classroom, but students can learn this dance for an unlimited time because this website is online. Not only students, anyone can learn this dance because the material uploaded to the website is directly connected to Youtobe. Keywords: Packaging, Audio Visual Media, Terang Bulan Learning Materials, Website ABSTRAK Penelitian ini bertujuan untuk mendeskripsikan tahapan pengemasan dan menghasilkan produk pembelajaran tari Terang Bulan dalam bentuk media audio visual berbasis Website untuk Kelas X Sekolah Menengah Atas.Teori-teori yang digunakan dalam topik penelitian yaitu teori pengemasan, materi pembelajaran, media audio visual dan Pembelajaran Berbasis Website. Teori yang digunakan dalam penelitian ini adalah Teori Langkah-langkah Pengemasan Materi Pembelajaran Berbasis Website menurut Lu’mu Tasri (2011:17). Populasi pada penelitian adalah Mahasiswa/i Prodi Pendidikan Tari stambuk 2015 dan sampel pada penelitian ini adalah 2 orang Mahasiswa/I Pendidikan Tari Stambuk 2015 dan Bibi Petti Manik selaku Narasumber pada penelitian ini. Teknik pengumpulan data meliputi observasi lapangan, wawancara, dokumentasi dan studi kepustakaan. Penelitian ini menggunkan metode deskriptif kualitatif. Analisis validasi ahli media dan validasi ahli materi memakai skala likert untuk menghitung rata-rata keseluruhannya. Penelitian ini dilaksanakan di Studio Tari Prodi Pendidikan Tari Jurusan Sendratasik Fakultas Bahasa dan Seni untuk proses pengemasan dilakukan di Laboratorium Prodi Pendidikan Tari Jurusan Sendratasik Fakultas Bahasa. Hasil Penelitian diketahui bahwa ada 10 tahapan dalam mengemas produk pembelajaran Materi Tari Terang Bulan bentuk media audio visual berbasis Website Untuk Kelas X Sekolah Menengah Atas terdiri dari (1) penentuan sasaran materi pembelajaran (2) pemilihan topik yang sesuai dengan kebutuhan sasaran (3) pembuatan peta materi (4) perumusan tujuan pembelajaran (5) penyusunan alat evaluasi (6) pengumpulan referensi (7) penyusunan bahan (8) editing (9) upload (10) testing. Pada tahap dilakukan validasi produk melibatkan 2 validator ahli materi dan 1 validator ahli media. Produk ini mendapat kategori sangat baik dengan rincian skor 4,6 dari uji validasi ahli materi, skor 4,8 dari uji validasi ahli media. Skor tersebut membuktikan bahwa produk video pembelajaran ini sangat baik untuk diterapkan dalam proses pembelajaran Seni Budaya khususnya bidang Seni Tari Kelas X SMA. Siswa dapat mempelajari tarian ini tidak hanya didalam proses KBM berangsung atau pada saat didalam kelas saja, akan tetapi siswa dapat mempelajari tarian ini dalam waktu yang tidak terbatas karena website ini bersifal online. Tidak hanya siswa, siapa saja pun dapat mempelajari tarian ini karena materi yang telah di unggah kedalam website langsung terhubung ke Youtobe. Kata kunci : Pengemasan, Media Audio Visual, Materi Pembelajaran Terang Bulan, Website